Typically developing adolescents' experience of growing up with a brother with an autism spectrum disorder. Issue 2 (3rd April 2017) - Corsano, Paola; Musetti, Alessandro; Guidotti, Laura; Capelli, Francesca
ABSTRACT: Background Researchers studying siblings of people with an autism spectrum disorder (ASD) suggest that growing up with an individual with disability has positive and negative effects. Method Qualitative content analysis of semistructured interviews with 14 typically developing (TD) adolescents with a brother with an ASD and their mothers was used to explore the experience of growing up with a sibling with an ASD and identify differences in the relationship with, and attitude toward, the brother. Results TD siblings expressed mixed feelings about their brother, a precocious sense of responsibility, concern about the future, friendship difficulties, and troubles and the desire to talk about their experience. Most adolescents integrated their positive and negative feelings; however, 3 adolescents displayed rejection, denial, or a sense of persecution. Conclusions Qualitative research into the experiences of adolescent siblings of people with an ASD should be used to develop support programs to help adolescents manage their relationship with a sibling with a disability.